A liaison model for disassembly-reassembly product ecodesign. (14th December 2009) - Mascle, Christian; Xing, Ke
This paper focuses on non-destructive disassembly for mechanical products as part of environment friendly manufacturing. An original approach using a clustering method for assembly and the introduction of a mathematical model, describing the fuzzy liaisons between the components, allow us to design the product for disassembly, service, recycling, upgrading and assembly. They also facilitate the determination of the problems related to the automation of assembly and disassembly sequences generation. To do so, the modelling of functional liaisons between parts helps to distinguish a simple contact from an attachment and subsets from subassemblies. Liaisons between components are described by matrices of fuzzy half degrees of liaison. The virtual locking liaisons could be extracted automatically from a B-rep model of a mechanical product on CAD and attachment liaisons are deduced from a fuzzy evaluation of their strength and condition changes.